The Inside of the Cup $1 (BVolume 06s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Inside of the Cup $1 (BVolume 06" by Winston Churchill is a novel published in 1913. Reverend John Hodder arrives at a prestigious church in a Midwestern city, expected to preach a comfortable Christianity to its wealthy patrons. But as he witnesses poverty and corruption surrounding the congregation, Hodder undergoes a spiritual crisis that forces him to choose between orthodox expectations and what he believes are Jesus's true teachings$1 (Ba decision that ignites conflict within his church and sparked nationwide debate upon the novel's release. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Inside_of_the_Cup
Release date is 2004-10-17
Produced by David Widger
Keywords: Christian life -- Fiction; Attitude change -- Fiction; Christian ethics -- Fiction; Conscience -- Religious aspects -- Fiction